Strongyloides stercoralis genotyping in a human population in southwestern Iran - Molouk Beiromvand; Alireza Ashiri; Veroni de Ree; Dorothee Harbecke; Christian Rödelsperger; Adrian Streit; Abdollah Rafiei (Parasites & Vectors, 2024)
Abstract Background Strongyloidiasis is a neglected tropical disease (NTD) that is caused mainly by Strongyloides stercoralis, with an estimated 600 million people infected worldwide, and in fewer cases by Strongyloides fuelleborni fuelleborni and Strongyloides fuelleborni kellyi. A number of studies have been conducted on the genetic diversity of S. stercoralis in East and Southeast Asia; however, there is very limited corresponding information from West Asian countries, including Iran. Methods For Strongyloides worms collected from patients in southwestern Iran, the hypervariable regions I (HVR-I) and IV (HVR-IV) of the nuclear 18S ribosomal DNA (rDNA) locus (SSU) and a fragment of the subunit 1 mitochondrial cytochrome c oxidase gene (cox-1) were sequenced. For a subset of the worms, whole-genome sequencing data were generated. Results The cox-1 sequences of 136 worms isolated from 23 patients indicated that all isolates were S. stercoralis. Among the cox-1 sequences, 33 polymorphic sites and 13 haplotypes were found. The phylogenetic analysis demonstrated that some sequences clustered fairly closely with sequences from humans and dogs from other parts of the world, while others formed a separate, Iran-specific group. Among 64 S. stercoralis analyzed, we found three of the previously described SSU HVR-I haplotypes, with haplotype II being the most frequent haplotype. In contrast to Southeast Asia, where S. stercoralis heterozygous for different haplotypes at the HVR-I locus are rare, we found 20 worms to be heterozygous for two different HVR-I haplotypes, 18 of which fell into the Iran-specific cox-1 cluster. SSU-heterozygous worms also showed elevated heterozygosity at the whole-genome level. Conclusions We conclude that the S. stercoralis population from the Khuzestan province shares much of the genetic diversity with the population in Southeast Asia, but there is an indication of additional genetic input. There appears to be some population structure with different subpopulations, which however do interbreed at least occasionally. Graphical Abstract